Interaction of an Outflow with Surrounding Gaseous Clouds as the Origin of Late-time Radio Flares in Tidal Disruption Events - Jialun Zhuang; Rong-Feng Shen; Guobin Mou; Wenbin Lu (The Astrophysical Journal)
Close encounter between a star and a supermassive black hole (SMBH) results in the tidal disruption of the star, known as a tidal disruption event (TDE). Recently, a few TDEs, e.g., ASASSN-15oi and AT2018hyz, have shown late-time (hundreds of days after their UV/optical peaks) radio flares with radio luminosities of 10 ^38∼39 erg s ^−1 . The super-Eddington fallback or accretion in a TDE may generate a mass outflow. Here, we investigate a scenario that the late-time radio flares come from the interaction of the outflow with the circumnuclear gaseous clouds, in addition to the slow-evolving emission component due to the outflow–diffuse medium interaction. We calculate the associated radio temporal and spectral signatures and find that they reproduce well the observations. The outflows have the inferred velocity of 0.2 c  ∼ 0.6 c , the total mass of 10 ^−3  ∼ 10 ^−1 M _⊙ and the ejection duration of a month to a year. The distances of the clouds to the SMBH are 0.1 ∼ 1 pc. This scenario has advantages in explaining the long delay, sharpness of the rise, and the multiplicity of the late radio flares. Future observations may build up a much larger sample of late-time radio flares and enable their use as a probe of the TDE physics and the host circumnuclear environment.